Examining the metonymic relation between a brand name and a product: A case study of Moroccan cosmetic brand names - Fatima Azzahraa El Yamlahi; María Enriqueta Cortés de los Ríos (Ibérica, 2022)
This paper takes a cognitive perspective on the semantics of Moroccan brand names, an unexplored territory so far, and analyzes the role of the metonymy in a corpus-based analysis in cosmetic brand names. More particularly, we focus on the following:   to shed some light on the metonymic cognitive operations in these names (domain expansion and domain reduction metonymies together with metonymic chains), to determine the occurrence frequency of metonymy in comparison to metaphor, to reveal the modes (visual, verbal) in which the brand names are manifested, and to examine if there is any connection between the type of cosmetics and the metonymic operations cued. In this light, the paper yields some significant findings: the most salient feature in our corpus is the low occurrence frequency of reduction metonymy that is largely outnumbered by its converse operations, expansion metonymy. Metonymic complexes are highly productive mechanisms for cosmetic brand-name creation, especially their significant presence in skincare and makeup brands. In this way, the conscious use of these mechanisms by brand designers can help in boosting brand identity and help in building a favorable brand image in an economical way.